Materials for production of protective boots for workers in forestry - Mikulčić, Miroslav (Array, 2019)
The effectiveness of forestry boots depends primarily on the materials of which they are made, the manner and location of incorporation. The use of highly sophisticated materials, highly developed technological processes and knowledge-based development provide a good basis for the production of quality forestry boots. This paper gives an overview of the technological phases of manufacturing forestry boots that meet the standards defining full human protection against mechanical and other injuries when using motor saws and possible crushing. The complexity of the manufacturing process of forestry boots is reflected in the use of special high-quality materials, their functions, and how to incorporate them into in the boot. To achieve full protection of the foot and lower leg, the forestry boot contains multi-layered advanced composite materials, appropriately processed leather, fabrics, steel, non-woven textiles, and waterproof and vapour-permeable membranes.